2004
DOI: 10.1242/dev.01068
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal signals produced by DAF-9/cytochrome P450 regulateC. elegansdauer diapause in response to environmental cues

Abstract: growth, off in dauer, hypodermal daf-9 expression is strictly daf-12 dependent, suggesting feedback regulation. Expressing daf-9 constitutively in hypodermis rescues dauer phenotypes of daf-9, as well as insulin/IGF receptor and TGFβ mutants, revealing that daf-9 is an important downstream point of control within the dauer circuits. This study illuminates how endocrine networks integrate environmental cues and transduce them into adaptive life history choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
168
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(180 citation statements)
references
References 54 publications
8
168
0
2
Order By: Relevance
“…The ncr-1; ncr-2 double mutants have reduced viability, gonadal migration defects, and constitutively form dauer larvae, a dormant life stage specialized for survival under harsh conditions (Sym et al 2000;Li et al 2004). The phenotypes of ncr-1; ncr-2 double mutants are similar to a class of ligand-binding domain mutants of daf-12, which encodes a nuclear steroid hormone receptor (Antebi et al 1998;Antebi et al 2000;Jia et al 2002;Gerisch and Antebi 2004;Li et al 2004). Li et al (2004) recently demonstrated that feeding cholesterol to animals mutant for ncr-1 and ncr-2 is sufficient to suppress the dauer phenotype associated with the loss of both genes.…”
Section: Discussionmentioning
confidence: 99%
“…The ncr-1; ncr-2 double mutants have reduced viability, gonadal migration defects, and constitutively form dauer larvae, a dormant life stage specialized for survival under harsh conditions (Sym et al 2000;Li et al 2004). The phenotypes of ncr-1; ncr-2 double mutants are similar to a class of ligand-binding domain mutants of daf-12, which encodes a nuclear steroid hormone receptor (Antebi et al 1998;Antebi et al 2000;Jia et al 2002;Gerisch and Antebi 2004;Li et al 2004). Li et al (2004) recently demonstrated that feeding cholesterol to animals mutant for ncr-1 and ncr-2 is sufficient to suppress the dauer phenotype associated with the loss of both genes.…”
Section: Discussionmentioning
confidence: 99%
“…Identified pathways regulating this decision include insulin/ IGF-1, TGF-b and cyclic GMP signalling. These signal transduction pathways converge on DAF-9, a cytochrome P450 steroid hydroxylase which is postulated to produce a cholestrol-derived hormone (Gerish and Antebi, 2004;Matyash et al, 2004). The target of this putative hormone is the nuclear hormone receptor DAF-12.…”
Section: Introductionmentioning
confidence: 99%
“…Expressing daf-9 constitutively in the hypodermis rescues the dauer arrest phenotypes of mutants defective in insulin/IGF-1 or TGF-b signalling, providing evidence that daf-9 integrates the outputs from these signalling pathways. However, some residual defects are observed in the rescued worms, suggesting that the dauer signalling pathways may also have some daf-9 independent outputs (Gerish and Antebi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These pathways converge on the nuclear hormone receptor DAF-12, which acts downstream of most Daf genes and which is expressed in many tissues that undergo remodeling during dauer formation (30). The TGF␤ and insulin pathways are thought to control DAF-12 in part by regulating enzymes (31)(32)(33)(34) involved in the biosynthesis of the DAF-12 steroid ligands (35,36). In addition to controlling the developmental and metabolic changes important for dauer formation, the TGF␤ and insulin pathways influence metabolism, stress resistance, and aging throughout the life cycle (27,(37)(38)(39).…”
mentioning
confidence: 99%